THE ROLE CORPORATE SOCIAL RESPONSIBILITY, CORPORATE ASSOCIATION AND BRAND LOVE TOWARDS WORD OF MOUTH INTENTION IN SUSTAINABLE RELATIONS IN THE INDONESIAN CELLULAR INDUSTRY - Emmanuel, Sandy; Saktiana, Galuh Mira; Nataherwin, Nataherwin (Graduate Program of Universitas Tarumanagara, 2024)
This research aims to examine the influence of corporate social responsibility (CSR), corporate association (CA) mediated by brand love on word of mouth (WOM) intention which has an impact on sustainable relationships in the cellular industry in Indonesia. This research only receives and manages data from respondents who use telecommunications services from 4 providers, namely XL, Indosat, Telkomsel and Three and are domiciled in JABODETABEK. Sampling used a non-probability sampling technique, namely convenience sampling, on 126 respondents, who live in JABODETABEK, users of telecommunications services from 4 providers, namely XL, Indosat, Telkomsel and TRI, using a questionnaire instrument in the form of a Google form . Then proceed with testing the validity test and reliability test as well as testing the hypothesis with the SEM-AMOS 22 analysis tool. The results of this research are that CSR has no effect on WOM Intention; CSA has no effect on WOM Intention; Brand Love influences WOM Intention; Brand Love does not mediate CSR on WOM; and Brand Love is proven to mediate CA on WOM Intention.